Effect of auxetic structures on crash behavior of cylindrical tube. (15th January 2019) - Lee, Wonjoo; Jeong, Yuhyeong; Yoo, Jesung; Huh, Hoon; Park, Sung-Jun; Park, Sung Hyuk; Yoon, Jonghun
Abstract: This paper mainly concerns effects of the auxetic structure on the crash performances in terms of the axial crash force, specific energy absorption, and deceleration, which are evaluated with the conventional and honeycomb structures. Based on the systematic design procedure, the re-entrant units for the auxetic structure are regularly arranged in the tube wall, which are produced by the additive manufacturing with SUS316L metal powder. Under the low impact condition, the auxetic does not only exhibit higher specific energy absorption, but also demonstrate substantially low deceleration due to effect of the densification during the axial crash compared with the conventional tube. Furthermore, while the honeycomb tube demonstrates oscillating behavior in the deceleration, the auxetic tube tends to maintain steady deceleration after the first peak during the axial crash, which is able to guarantee enhanced damping performances under the low impact condition.